Animal Studies, Indigenous Spacecraft - Shukin, Nicole (FRAME, Journal of Literary Studies, 2026)
With the future of all species on Earth under threat within the Capitalocene, what can Animal Studies learn about struggles for futurity from Indigenous authors and artists? This article proposes that the genre of Indigenous Futurism (IF) can guide Animal Studies to decolonize the art and act of imagining multispecies futures, in part by reviving arts of time-space travel practiced by Indigenous people in relation with both animals and aliens. Contrasting Indigenous Futurisms with the dangerously literal technologies of space and time-travel represented by actors as diverse as the poet Christian Bök and NASA can be instructive for Animal Studies.